Effects of prolonged local vibration superimposed to muscle contraction on motoneuronal and cortical excitability - Pfenninger, Clara; Grosboillot, Nathan; Digonet, Guillaume; Lapole, Thomas (Frontiers in Physiology, 2023)
Acute effects of prolonged local vibration (LV) at the central nervous system level have been well investigated demonstrating an altered motoneuronal excitability with a concomitant increase in cortical excitability. While applying LV during isometric voluntary contraction is thought to optimize the effects of LV, this has never been addressed considering the acute changes in central nervous system excitability. In the present study, nineteen healthy participants were engaged in four randomized sessions. LV was applied for 30 min to the relaxed flexor carpi radialis muscle (VIBRELAXED) or during wrist flexions (i.e. intermittent contractions at 10% of the maximal voluntary contraction: 15 s ON and 15 s OFF; VIBCONTRACT). A control condition and a condition where participants only performed repeated low-contractions at 10% maximal force (CONTRACT) were also performed. For each condition, motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation and cervicomedullary evoked potentials (CMEPs) elicited by corticospinal tract electrical stimulation were measured before (PRE) and immediately after prolonged LV (POST) to investigate motoneuronal and corticospinal excitability, respectively. We further calculated the MEP/CMEP ratio as a proxy of cortical excitability. No changes were observed in the control nor CONTRACT condition. At POST, CMEP decreased similarly in VIBRELAXED (- 32% ± 42%, p < 0.001) and VIBCONTRACT (- 41% ± 32%, p < 0.001). MEP/CMEP increased by 110 ± 140% (p = 0.01) for VIBRELAXED and by 120 ± 208% (p = 0.02) for VIBCONTRACT without differences between those conditions. Our results suggest that LV to the flexor carpi radialis muscle, either relaxed or contracted, acutely decreases motoneuronal excitability and induces some priming of cortical excitability.